Experience with two antimicrobial prescribing tools in ambulatory care settings - Zahra Kassamali Escobar; Scott Thomasson; Todd Bouchard; Staci Kvak; Kyung Min Lee; Jose Mari Lansang; John B. Lynch; Larissa May; Marisa D'Angeli; Chloe Bryson-Cahn (Cambridge University Press, 2022)
We compared experiences with The Multifaceted Intervention to Improve Prescribing for Acute Respiratory Infection for Adult and Children in Emergency Department and Urgent Care Settings versus Choosing Wisely to evaluate inappropriate antimicrobial prescribing in ambulatory care. Both identified the same clinics, diagnoses, and antibiotics for high-yield antibiotic stewardship interventions.